Changes in Volatile Compounds and Sensory Properties of Chicken with Armillaria mellea During the Pressure-Cooking Process - Xiaolan Dong; Chuntao Xia; Hongxiu Fan; Xu Zhang; Tong Sun; Zhiyu Wang; Tingting Liu (Foods)
Chicken with Armillaria mellea prepared via pressure cooking is a traditional Chinese delicacy with great potential for food development. Optimizing its cooking time is crucial. In this study, chicken and Armillaria mellea were pressure-cooked for different amounts of time (20 min, 25 min, 30 min, 35 min, and 40 min). In total, 101 and 81 volatile compounds were identified by GC-MS and GC-IMS, respectively. The results showed that the content of volatile compounds was the highest at 40 min. Nonanal, decanal, (E,E)-2,4-nonadienal, (E,E)-2,4-decadienal, and 1-octen-3-ol were identified as the most critical aroma compounds at this time, which brought unique fat, oil, and mushroom aroma to chicken with Armillaria mellea during the pressure-cooking process. The optimal time was determined to be 35 min through sensory properties. In summary, the optimal cooking time for chicken with Armillaria mellea prepared via pressure cooking is 35–40 min. Our research results not only preliminarily determined the optimal conditions for industrial processing of the prepared dish of with Armillaria mellea prepared via pressure cooking, laying a foundation for the later industrial production of prepared dishes and international sales, but also stimulated innovative composite food development and promoted people’s exploration of the mechanism of heat treatment on composite food flavor and taste.